2015
DOI: 10.1002/btpr.2089
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring recombinant protein quality by rational media design

Abstract: Clinical efficacy and safety of recombinant proteins are closely associated with their structural characteristics. The major quality attributes comprise glycosylation, charge variants (oxidation, deamidation, and C‐ & N‐terminal modifications), aggregates, low‐molecular‐weight species (LMW), and misincorporation of amino acids in the protein backbone. Cell culture media design has a great potential to modulate these quality attributes due to the vital role of medium in mammalian cell culture. The purpose of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 281 publications
(483 reference statements)
0
55
0
Order By: Relevance
“…Finally, numerous previous studies have demonstrated the impact of media on glycosylation (Brühlman et al, 2015; Hossler et al, 2014; Surve and Gadgil, 2015). Thus, it will be of great value to integrate our model with models of other metabolic pathways.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Finally, numerous previous studies have demonstrated the impact of media on glycosylation (Brühlman et al, 2015; Hossler et al, 2014; Surve and Gadgil, 2015). Thus, it will be of great value to integrate our model with models of other metabolic pathways.…”
Section: Discussionmentioning
confidence: 91%
“…Experimental control strategies, including genetic modifications and media additives, have been used to manipulate glycosylation (Brühlman et al, 2015; Shi and Goudar, 2014; Sou et al, 2014; St Amand et al, 2014), but so far a systematic understanding of these strategies is largely lacking. Therefore, computational models of glycosylation carry a great potential in elucidating control strategies in a rational and cost-efficient manner.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing evidence for product alterations through chemical conjugations or modifications ascribable to cell culture medium reaction products supports the need for novel approaches to define and monitor CDM quality . At present, Raman and fluorescence spectroscopy in combination with chemometric tools represent the most commonly used methods to examine alterations in cell culture media batches .…”
Section: Introductionmentioning
confidence: 99%
“…The achievable cell density, titer, metabolism and culture duration is dependent on the compositions of cell culture media [3]. For the predominantly used Chinese hamster ovary (CHO) cells, research shows that individual components of mammalian cell culture media (CCM), even in trace amounts, influence the post translational modifications crucial to the function of the recombinant proteins produced [4][5][6]. The formulation of these media is done in small scale in liquid using stock solution of ingredients.…”
Section: Introductionmentioning
confidence: 99%